Assessment of the Relationship Between Cost of Building Materials and Property Development in Abia State, Nigeria: Evidence from Trends in Cost of Building Materials and Property Development - Ihedigbo, Kingsley Sunday; Mgbeahuru, Christian Obinna; Wuna, Mohammed Abubakar; Olughu, Christopher Egwu (Journal of Sustainability and Environmental Management, 2024)
Building materials contribute immensely to the quality and cost of any construction project. It is therefore pertinent for stakeholders in the construction industry to understand the implication of the rise in price of building materials and its influence on property development. The poor performance of the construction industry in terms of project delay and abandonment has been linked to incessant increase in the price of building materials. This study therefore, aims to assess the relationship between cost of building materials and property development in Abia State in order to address the challenges of building deficits in Nigeria. The study employed a quantitative research approach through a questionnaire survey that was conducted among the various construction professionals and material dealers. A total of one hundred (100) questionnaires were distributed, resulting in 77 valid responses, which is considered adequate for analysis. The study revealed that cost of building materials has a positive and statistically significant relationship with property development, with a p-value of <.022. This indicate that cost of building materials determines the level of property development. Thus, in order to overcome the challenges of project delay, project abandonment and housing deficits resulting from the incessant rise in cost of building materials, the study recommended that urgent attention should be given to the various factors influencing the cost of building materials. Also, adequate and functional price control agencies and policy should be put in place in order to regulate and checkmate the unnecessary price hike on building materials in the country.